ANALYSIS OF INFORMAL COMMUNICATION NETWORKS IN HARDCORE VIOLENCE YOUTH CREW 253 COMMUNITY - Rizq Iskandar, Rayhan; Rochmaniah, Ainur (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze informal communication networks in the hardcore violence youth crew 253 community in Sidoarjo. The relationships between individuals in the community form a communication network that reflects the social structure and pattern of information dissemination. By understanding these patterns, the communication process can be carried out more effectively and efficiently. Method: The method used is a quantitative approach by involving 30 community members who are active in various activities, such as concerts and discussions. Data was collected through questionnaires and in-depth interviews, and then analyzed using the UCINET application to measure various network metrics, including density, eigenvector centrality, degree centrality, and betweenness centrality. Results: The results of the analysis showed that the communication network in this community has a fairly high level of attachment with a density value of 57%. The actor with the highest eigenvector centrality value is Falah, which acts as the main link in the dissemination of information. In addition, it was found that several actors play a crucial role in accelerating the flow of communication. The communication patterns formed in this network follow the gossip sequence communication pattern, which reflects the informal and organic character of the interaction dynamics within the community. Novelty: This study reveals the specific informal communication patterns within a hardcore youth crew, highlighting the key actors and their roles in information dissemination, as well as the organic, gossip-based interaction dynamics unique to this community.